The Effect of Music Therapy (Mozart) on Hallucination Frequency in Patients with Auditory Hallucinations at A Mental Hospital - Novarianty, Cici; Priyono, Djoko; Usman, Usman (Universitas Tanjungpura, 2025)
Background: Hallucination is a disturbance of sensory perception without external stimuli, involving all sensory systems and occurring while the individual’s consciousness is intact. There are several forms of hallucination, including visual, auditory, tactile, gustatory, and olfactory. Auditory hallucination is a perceptual disturbance in which the client perceives something that is not actually occurring. Hallucinations can be managed with pharmacological and non-pharmacological therapy; one effective non-pharmacological therapy is listening to classical music (Mozart). Objective: To determine the effect of music therapy (Mozart) on hallucination frequency in patients with auditory hallucinations at the West Kalimantan Provincial Mental Hospital. Methods: This quantitative study used a quasi-experimental pretest-posttest control group design with 32 respondents. The instrument was a questionnaire of two items on hallucination frequency, adapted from the signs and symptoms of hallucination questionnaire in Wahyuni (2010), itself adapted from the Psychotic Symptom Rating Scale (PSYRATS) developed by Haddock et al. (1991) in Kingdon & Turkington (2008). Data were analysed using the paired t-test. Results: After music therapy (Mozart) was given to patients with auditory hallucinations, a change in hallucination frequency was shown by the paired t-test (p<0.0001). Conclusion: There is an effect of music therapy (Mozart) on hallucination frequency in patients with auditory hallucinations at the West Kalimantan Provincial Mental Hospital. Therefore, music therapy (Mozart) can be recommended to help reduce hallucination frequency in patients with auditory hallucinations.